The Transformation of Da’wah Institutions: Developing Entrepreneurial Products in the Disruptive Era - Darmawati, Nia; Castrawijaya, Cecep (Abdurrauf Journal of Islamic Studies, 2025)
The disruptive era presents both challenges and opportunities for Islamic preaching institutions in maintaining their existence and relevance within modern society. Changes in communication patterns, digital content competition, limited human resources, and dependency on donations have driven the need for transformation in da’wah management. This study aims to analyze the transformation strategies of Islamic preaching institutions through the development of entrepreneurship-based products grounded in Islamic values. The research employs a qualitative descriptive approach through a literature review, examining studies related to digital da’wah, social entrepreneurship, and religious institution management. The findings indicate that digitalization of da’wah, cross-sector collaboration, human resource capacity building, service diversification, and the integration of da’wah values into creative products are strategic steps to adapt to the disruptive era. The entrepreneurial products developed can take the form of digital, physical, or service-based outputs that promote community empowerment. The implementation of entrepreneurship strengthens institutional sustainability, enhances da’wah effectiveness, creates economic independence, opens job opportunities, and fosters a positive image of Islamic institutions as modern, adaptive, and solution-oriented entities. Therefore, entrepreneurship serves as a vital instrument to ensure the continuity of da’wah while holistically addressing societal needs. [Era disruptif menghadirkan tantangan sekaligus peluang bagi lembaga dakwah dalam menjaga eksistensi dan relevansinya di tengah dinamika masyarakat modern. Perubahan pola komunikasi, persaingan konten digital, keterbatasan sumber daya manusia, serta ketergantungan pada donasi menjadi faktor yang mendorong perlunya transformasi dalam pelaksanaan dakwah. Artikel ini bertujuan untuk menganalisis strategi transformasi lembaga dakwah melalui pengembangan produk kewirausahaan yang berlandaskan nilai-nilai Islam. Metode penelitian yang digunakan adalah studi kepustakaan dengan pendekatan deskriptif kualitatif yang menelaah berbagai literatur terkait dakwah digital, kewirausahaan sosial, dan manajemen lembaga keagamaan. Hasil kajian menunjukkan bahwa digitalisasi dakwah, kolaborasi lintas sektor, penguatan kapasitas sumber daya manusia, diversifikasi layanan, serta integrasi nilai dakwah dalam produk kreatif merupakan langkah strategis untuk beradaptasi dengan era disruptif. Produk kewirausahaan yang dikembangkan dapat berupa produk digital, fisik, maupun jasa yang mendukung pemberdayaan umat. Implementasi kewirausahaan terbukti mampu memperkuat eksistensi lembaga dakwah, mewujudkan kemandirian ekonomi, meningkatkan efektivitas dakwah, membuka lapangan kerja, serta membangun citra positif sebagai lembaga yang modern, adaptif, dan solutif. Dengan demikian, kewirausahaan berperan sebagai instrumen penting dalam menjamin keberlanjutan dakwah sekaligus menjawab kebutuhan masyarakat secara holistik.]